2020
DOI: 10.15252/embr.201949634
|View full text |Cite
|
Sign up to set email alerts
|

Blocking mitochondrial pyruvate import in brown adipocytes induces energy wasting via lipid cycling

Abstract: Combined fatty acid esterification and lipolysis, termed lipid cycling, is an ATP‐consuming process that contributes to energy expenditure. Therefore, interventions that stimulate energy expenditure through lipid cycling are of great interest. Here we find that pharmacological and genetic inhibition of the mitochondrial pyruvate carrier (MPC) in brown adipocytes activates lipid cycling and energy expenditure, even in the absence of adrenergic stimulation. We show that the resulting increase in ATP demand eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 68 publications
0
30
0
Order By: Relevance
“…On the other hand, the glutaminolysis and β -oxidation seem equally overactivated when mitochondrial catabolism of pyruvate is substantially decreased. Veliova et al discovered that pharmacological inhibition of mitochondrial pyruvate carrier (MPC) in brown adipocytes was sufficient to increase ATP synthesis fueled by mFAO and ATP consumption by FAS [ 227 ]. Furthermore, they found that glutamine consumption and the malate-aspartate shuttle were necessary to increase the energy expenditure caused by MPC inhibition.…”
Section: Additional Factors That Could Interfere With the “ ...mentioning
confidence: 99%
“…On the other hand, the glutaminolysis and β -oxidation seem equally overactivated when mitochondrial catabolism of pyruvate is substantially decreased. Veliova et al discovered that pharmacological inhibition of mitochondrial pyruvate carrier (MPC) in brown adipocytes was sufficient to increase ATP synthesis fueled by mFAO and ATP consumption by FAS [ 227 ]. Furthermore, they found that glutamine consumption and the malate-aspartate shuttle were necessary to increase the energy expenditure caused by MPC inhibition.…”
Section: Additional Factors That Could Interfere With the “ ...mentioning
confidence: 99%
“…Recently, Veliova et al proposed a novel mechanism to activate lipid cycling and increase energy dissipation in non-stimulated brown adipocytes, by blocking the mitochondrial pyruvate carrier (MPC) (Fig. 1) [84]. Inhibition of the MPC results in increased ATP demand and coupled mitochondrial fat oxidation to support fatty acid esterification, as energy expenditure was sensitive to the ACS inhibitor Triacsin C. Consequently, MPC blockage increases fat oxidation and energy expenditure bypassing the need for adrenergic stimulation or mitochondrial uncoupling to oxidize fat [84].…”
Section: Mechanisms Inducing Lipid Cyclingmentioning
confidence: 99%
“…1) [84]. Inhibition of the MPC results in increased ATP demand and coupled mitochondrial fat oxidation to support fatty acid esterification, as energy expenditure was sensitive to the ACS inhibitor Triacsin C. Consequently, MPC blockage increases fat oxidation and energy expenditure bypassing the need for adrenergic stimulation or mitochondrial uncoupling to oxidize fat [84]. It remains to be determined whether lipid cycling can be induced in white adipocytes by a similar mechanism, which would be particularly interesting as a way to promote energy-wasting and possibly weight loss.…”
Section: Mechanisms Inducing Lipid Cyclingmentioning
confidence: 99%
“…While the metabolic benefit of interrupting normal pyruvate use in glucose-consuming tissues, such as skeletal muscle, may seem counterintuitive, impairing mitochondrial pyruvate flux in the liver is beneficial in certain disease states by reducing gluconeogenesis ( 16 , 17 , 18 ). Moreover, inhibition of the MPC also stimulates fat oxidation and compensatory use of amino acids by the liver ( 7 , 16 ), brown adipose tissue ( 19 , 20 ), and skeletal muscle ( 21 ).…”
mentioning
confidence: 99%